Microsatellite markers for Anthericum ramosum: Development, characterization, and cross‐species amplification. (14th February 2020) - Vít, Petr; Krak, Karol; Douda, Jan; Mandák, Bohumil
Abstract : Premise: A set of polymorphic nuclear microsatellite loci was developed and tested for use in population genetic analyses of Anthericum ramosum (Agavaceae) and related species. Methods and Results: Sequences of 110 primers were extracted in silico from Illumina MiSeq genome skimming data. The degree of polymorphism of 19 loci was tested in four A . ramosum populations collected in Central and Eastern Europe. The average number of alleles per loci ranged from two to 17, and levels of observed and expected heterozygosity ranged from 0.000 to 1.000 and from 0.100 to 0.900, respectively. Primers were successfully amplified in the closely related species A. liliago (12 loci) and Chlorophytum comosum (six loci), whereas they mostly failed to amplify in the phylogenetically more‐distant species Muscari comosum (three loci) and M . tenuiflorum (no amplification). Conclusions: This newly developed set of polymorphic nuclear microsatellite markers will be useful for population genetic investigation of A . ramosum and closely related species.